Clinic-based prevalence and husbandry-associated factors of radiographically confirmed urolithiasis among pet tortoises in Jakarta - Nathanael Yosafat Hartanto; Tetty Barunawati Siagian; Muhammad Piter Kombo (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2026)
Bladder stone is one of the most frequently encountered urological disorders in land tortoises kept as pets, closely related to husbandry practices. This retrospective clinic-based study estimated the prevalence of radiographically confirmed bladder stones and explored associated husbandry factors in pet tortoises examined at an exotic animal clinic in Jakarta. Medi-cal records of 42 land tortoises examined between October 4 and December 1, 2025, were reviewed. The extracted data included species, diet, water access, housing system, clinical findings, and radiographic results. Seven tortoises were diagnosed with bladder stones, giving a clinic-based prevalence of 16.7% (7/42). All affected tortoises were Centrochelys sulcata. In univariable exact analyses, species was associated with bladder stone occurrence, whereas diet, water access, and housing showed uncertain associations because of small subgroup sizes and missing data. These findings suggest that C. sulcata presented to exotic animal clinics may warrant routine radiographic screening, but larger multicenter studies are needed to clarify the role of husbandry factors.